The role and potential therapeutic targets of astrocytes in central nervous system demyelinating diseases - Tan, Rui; Hong, Rui; Sui, Chunxiao; Yang, Dianxu; Tian, Hengli; Zhu, Tao; Yang, Yang (Frontiers in Cellular Neuroscience, 2023)
Astrocytes play vital roles in the central nervous system, contributing significantly to both its normal functioning and pathological conditions. While their involvement in various diseases is increasingly recognized, their exact role in demyelinating lesions remains uncertain. Astrocytes have the potential to influence demyelination positively or negatively. They can produce and release inflammatory molecules that modulate the activation and movement of other immune cells. Moreover, they can aid in the clearance of myelin debris through phagocytosis and facilitate the recruitment and differentiation of oligodendrocyte precursor cells, thereby promoting axonal remyelination. However, excessive or prolonged astrocyte phagocytosis can exacerbate demyelination and lead to neurological impairments. This review provides an overview of the involvement of astrocytes in various demyelinating diseases, emphasizing the underlying mechanisms that contribute to demyelination. Additionally, we discuss the interactions between oligodendrocytes, oligodendrocyte precursor cells and astrocytes as therapeutic options to support myelin regeneration. Furthermore, we explore the role of astrocytes in repairing synaptic dysfunction, which is also a crucial pathological process in these disorders.